A Novel Microglia-Specific Transcriptional Signature Correlates With Behavioral Deficits in Neuropsychiatric Lupus - Makinde, Hadijat M.; Winter, Deborah R.; Procissi, Daniele; Mike, Elise V.; Stock, Ariel D.; Kando, Mary J.; Gadhvi, Gaurav T.; Droho, Steven; Bloomfield, Christina L.; Dominguez, Salina T.; Mayr, Maximilian G.; Lavine, Jeremy A.; et al. (Frontiers in Immunology, 2020)
Neuropsychiatric symptoms of systemic lupus erythematosus (NP-SLE) affect over one-half of SLE patients, yet underlying mechanisms remain largely unknown. We demonstrate that SLE-prone mice (CReCOM) develop NP-SLE, including behavioral deficits prior to systemic autoimmunity, reduced brain volumes, decreased vascular integrity and brain-infiltrating leukocytes. NP-SLE microglia exhibit numerical expansion, increased synaptic uptake and a more metabolically active phenotype. Microglia from multiple SLE-prone models express a ‘NP-SLE signature’ unrelated to type I interferon. Rather, the signature is associated with lipid metabolism, scavenger receptor activity and downregulation of inflammatory and chemotaxis processes, suggesting a more regulatory, anti-inflammatory profile. NP-SLE microglia also express genes associated with disease-associated microglia (DAM), a subset of microglia thought to be instrumental in neurodegenerative diseases. Further, expression of ‘NP-SLE’ and ‘DAM’ signatures correlate with the severity of behavioral deficits in young SLE-prone mice prior to overt systemic disease. Our data are the first to demonstrate the predictive value of our newly identified microglia-specific ‘NP-SLE’ and ‘DAM’ signatures as a surrogate for NP-SLE clinical outcomes and suggests that microglia-intrinsic defects precede contributions from systemic SLE for neuropsychiatric manifestations.